SISTEM INFORMASI MANAJEMEN TATA KELOLA SURAT MENYURAT BERBASIS WEB DI SMP N 19 KABUPATEN PESAWARAN - Puspitasari, Tuti; Wicaksono, Priambagus; Irviani, Rita (STIT AL MULTAZAM, 2023)
This research was conducted to develop a more computerized filing system at SMP N 19 Pesawaran District. The purpose of this research is to add the Correspondence feature to the existing system because the use of a mailing system that is still manual and prone to losing letters can cause loss of time, costs, and hinder administrative processes at schools. The waterfall method and programming languages PHP, Java Script, and CSS are used in the development of information systems that have correspondence features. This system is useful in the process of storing and reporting incoming and outgoing letters contained in the agenda book. The author adds a special menu to back up letters stored in the information system. This backup feature is very important to ensure the security and retention of data stored in information systems. With the data backup and agenda letter features, the process of managing incoming and outgoing mail archives can be done more effectively and efficiently. This can help improve overall organizational efficiency and productivity. In this study, the authors succeeded in developing an information system that is more computerized and integrated with the Correspondence feature which is safe, reliable, and easy for users to use. This research has the potential to improve the quality of administrative services at SMP N 19 Pesawaran District and can be adopted by similar institutions to improve letter filing and increase overall organizational productivity.